Evaluasi Program Ujian Akhir Semester (UAS) Virtual Model Cipp (Context, Input, Process, Product) di IAINU Kebumen Tahun Akademik 2019/2020 - Atim Rinawati; Imam Subarkah (LPPM IAINU Kebumen, 2020)
This study aims to find out: 1) To find out how the evaluation stages of the virtual UAS program at IAINU Kebumen College are with the CIPP model. 2) To find out the effectiveness and efficiency of implementing virtual UAS at IAINU Kebumen. This research is an evaluation research (evaluation research) with the research object of implementing the Virtual Semester Final Examination (UAS) program at IAINU Kebumen Higher Education, which is carried out by all faculties at IAINU Kebumen. The data sources in this study were the Deputy Chancellor 1 for Academic and Student Affairs, the Coordinator for the implementation of the Virtual UAS and students who participated in the first Virtual UAS in 2019 at IAINU Kebumen Higher Education. Students who were sampled using the Cluster Random Sampling technique, the evaluation model used was the CIPP evaluation model with the quantitative evaluation method. Data collection was taken through questionnaires, interviews and documentation. Data analysis uses descriptive statistics and is presented in the form of tables and histograms. The results of this research are the stages of program evaluation carried out by researchers according to program evaluation procedures, namely the planning stage, the implementation stage, the monitoring stage, the interpretation data analysis stage and the recommendation preparation stage. After the data analysis process was completed, the research results showed that the evaluation of the virtual UAS program at IAINU Kebumen for the 2019/2020 Academic Year was as follows: the percentage of evaluation of context showed good results with a percentage of 75.20%, the percentage of evaluation of input showed results which is classified as good, namely 68.37%, the percentage of evaluation of the process shows results that are classified as good, namely 71.50%, the percentage of evaluation of the product shows results that are classified as good, namely 73.28%. Based on the results of this study it can be concluded that the implementation of the virtual UAS in terms of all aspects, namely context, input, process, product is classified as good with a percentage yield of 72.09%. Based on this percentage, the implementation of virtual UAS can be said to be effective and efficient. So, the recommendations that the authors can give to decision makers are (1) improving the virtual UAS supporting facilities and infrastructure; (2) minimize the occurrence of disturbances in the system used as a virtual UAS media; (3) improve the security of answers so that plagiarism does not occur.